2008
DOI: 10.1111/j.1473-2165.2008.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of keloids and hypertrophic scars using bleomycin

Abstract: Bleomycin is easy to administer, is cheap, shows high regression rate, and has minimum complication and recurrence. Thus, it can be used as the first-line treatment modality for management of keloids and hypertrophic scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 21 publications
2
50
1
Order By: Relevance
“…This resulted in complete flattening in 22 patients (44%), significant flattening in 11 patients (22%), adequate flattening in 7 patients (14%) and no flattening in 10 patients (20%). The difference between the present study and that of Aggarwal et al (2008) may be due to the difference in the methods of injection. It could be concluded that intralesional injection of bleomycin is more effective than the superficial puncture techniques.…”
Section: Espana Et Al (2001) Used Intralesional Bleomycin Injection contrasting
confidence: 54%
See 1 more Smart Citation
“…This resulted in complete flattening in 22 patients (44%), significant flattening in 11 patients (22%), adequate flattening in 7 patients (14%) and no flattening in 10 patients (20%). The difference between the present study and that of Aggarwal et al (2008) may be due to the difference in the methods of injection. It could be concluded that intralesional injection of bleomycin is more effective than the superficial puncture techniques.…”
Section: Espana Et Al (2001) Used Intralesional Bleomycin Injection contrasting
confidence: 54%
“…Complete flattening was seen in 6 patients, highly significant flattening (>90%) was observed in 6 patients, and significant flattening (75%-90%) in 1 patients. Also, Aggarwal et al (2008) used bleomycin by multiple superficial puncture technique to treat fifty patients with keloids and hypertrophic scars. Three applications were given at interval of fifteen days followed by a fourth and final application two months after the last application.…”
Section: Espana Et Al (2001) Used Intralesional Bleomycin Injection mentioning
confidence: 99%
“…Ulceration healed within 10 days and hyperpigmentation resolved after 1 year of follow up. 44,45 None of the patients demonstrated any pulmonary, hepatic, or other major sideeffect of bleomycin, which may due to low dose of this drug. The recurrence reported by Himanshu was about 14% over 18 months of follow-up, which is similar to results shown by Espana (15.4%).…”
Section: Bleomycin Injectionmentioning
confidence: 97%
“…Injected bleomycin was effective at causing flattening of keloid scars in two noncontrolled studies. 126,127 Pressure therapy. Pressure garments are a commonly used conservative therapeutic option for scars and are particularly popular for large burn scars.…”
Section: Stem Cells In 2009 Biernaskie Et Al Deter-mentioning
confidence: 99%